Nano Hard Carbon Anodes for Sodium-Ion Batteries - Kim, Dae-Yeong (Nanomaterials (Basel), 2019)
A hindrance to the practical use of sodium-ion batteries is the lack of adequate anode materials. By utilizing the co-intercalation reaction, graphite, which is the most common anode material of lithium-ion batteries, was used for storing sodium ion. However, its performance, such as reversible capacity and coulombic efficiency, remains unsatisfactory for practical needs. Therefore, to overcome these drawbacks, a new carbon material was synthesized so that co-intercalation could occur efficiently. This carbon material has the same morphology as carbon black; that is, it has a wide pathway due to a turbostratic structure, and a short pathway due to small primary particles that allows the co-intercalation reaction to occur efficiently. Additionally, due to the numerous voids present in the inner amorphous structure, the sodium storage capacity was greatly increased. Furthermore, owing to the coarse co-intercalation reaction due to the surface pore structure, the formation of solid-electrolyte interphase was greatly suppressed and the first cycle coulombic efficiency reached 80%. This study shows that the carbon material alone can be used to design good electrode materials for sodium-ion batteries without the use of next-generation materials.